2004
DOI: 10.1111/j.1346-8138.2004.tb00627.x
|View full text |Cite
|
Sign up to set email alerts
|

Odontogenic Sinus Tract to the Neck Skin: A Case Report

Abstract: We describe a 22-year-old woman with neck skin sinus tract that developed as a consequence of dental infection. The patient was treated twice in an inappropriate way with recurrence of the sinus tract. We opted for an extraction of the tooth. This case illustrates the need for cooperative diagnostic referrals between physicians and dentists.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Differential diagnosis of cutaneous draining sinus tract should include suppurative apical periodontitis, osteomyelitis, traumatic lesions, congenital fistula, salivary gland fistulas and infected cyts, deep mycotic infections and gumma of tertiary syphilis. In addition, skin lesions such as pustules and furuncles, foreign-body lesions, squamous cell carcinoma and granulomatous disorders may all be similar superficially in appearance to draining sinus tracts of dental origin, but they are not true sinus tracts ( 1 , 2 , 4 , 6 , 7 , 12 , 14 , 18 ).The principle of managing such lesions is to remove the source of dental infection ( 9 , 14 , 16 ). Unless the dental focal infection is treated, recurrence is likely ( 5 , 10 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Differential diagnosis of cutaneous draining sinus tract should include suppurative apical periodontitis, osteomyelitis, traumatic lesions, congenital fistula, salivary gland fistulas and infected cyts, deep mycotic infections and gumma of tertiary syphilis. In addition, skin lesions such as pustules and furuncles, foreign-body lesions, squamous cell carcinoma and granulomatous disorders may all be similar superficially in appearance to draining sinus tracts of dental origin, but they are not true sinus tracts ( 1 , 2 , 4 , 6 , 7 , 12 , 14 , 18 ).The principle of managing such lesions is to remove the source of dental infection ( 9 , 14 , 16 ). Unless the dental focal infection is treated, recurrence is likely ( 5 , 10 ).…”
Section: Discussionmentioning
confidence: 99%
“…Clinically, these lesions appear as a papule or nodule, 1 mm to 20 mm in diameter with purulent discharge, usually on the chin or in the submental region ( 1 , 3 , 4 , 7 , 16 , 18 ). The other uncommon locations are cheek, canine space, nasolabial fold, nostrils, neck and inner canthus of eye ( 5 , 7 , 9 , 17 , 18 ). Palpation of the involved area often reveals a cordlike tract attached to the underlying alveolar bone in the area of suspected tooth.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cutaneous odontogenic sinus tracts of dental origin are uncommon. Although they have been well documented in the medical and dental literature, these lesions continue to be often misdiagnosed, challenging and pose a diagnostic dilemma (Cohenca et al, 2003;Susic et al, 2004). Studies revealed that the extra-oral sinus tracts are most commonly found on the cheek, chin and angle of the mandible (Slutzky-Goldberg et al, 2009;Magliocca et al, 2010;Vyas and Chaturvedi, 2011).…”
Section: Introductionmentioning
confidence: 99%